Macroeconomic factor, firm characteristics and inventory holding in Nigeria: A quantile regression approach - Egbunike, Chinedu Francis; Oranefo, Patricia Chinyere (International Journal of Financial, Accounting, and Management, 2023)
Purpose: Prior studies show that inventory holding is closely linked to liquidity and procyclical dependent on the combination of macroeconomic and firm characteristics. Thus, conditional linear factor models such as OLS should fail to explain the inventory-holding motive, especially in the context of developing countries. This study seeks to empirically investigate the determinants of corporate inventory holding based on evidence from pharmaceutical companies in Nigeria. Research methodology: The study adopts the ex post facto research design. The final sample was eight pharmaceutical & healthcare firms quoted on the Nigerian Stock Exchange (NSE). The data were analysed using the quantile regression technique. Results: The results showed that the inflation rate had a positive effect on the inventory holding distribution at upper quantiles (75th); and, the cash conversion cycle on the inventory holding was significant at different quantiles (25th, 50th and 75th). Profitability and liquidity were non-significant at different quantile distributions. Limitations: The focus on pharmaceutical firms limits the generalizability of the study findings to other sectors of the economy. Contributions: The study contributes to the literature in the context of developing countries, on the impact of varying firm characteristics and inflation rates on the different conditional distribution of the regressand, i.e., inventory holding.